Osteoporosis and bone metabolism in cirrhotic patients - Enver GÜREL; Mahmut ÖZTÜRK; Macit GÜLTEN; Selim Giray NAK; Enver DOLAR; Yusuf KARAARSLAN; Faruk MEMİK (Turkish Journal of Gastroenterology, 2019)
-